Appropriate Roles for the Subscriber, Publisher, Editor, Author, and Reviewer in the Archives of Plastic Surgery - Kun Hwang (Archives of Plastic Surgery, 2013)
Authors, editors and reviewers, publishers, and subscribers all play their role in scientific journals. These 5 stakeholders are essential to journals. In this paper, firstly, I briefly summarize the role of each journal stakeholder and their respective goals. Secondly, the status of each participant in the Archives of Plastic Surgery is described. Finally, I propose an appropriate role and plan for each of them. Specific roles and responsibilities include the following: subscribers should welcome and submit the critiques of published papers in letters to the editor. Publishers should trust editors and provide them with adequate financial support for ongoing quality improvement of the journal. The editor-in-chief should be given a sufficient period of time-several years-to build up journal quality and train the incoming editor. The editors, including section editors, are also responsible for increasing the author pool. One editor might be designated a 'devil's referee', that is, a kind of devil's advocate with the responsibility of examining the originality of the manuscript, taking a skeptical view of the manuscript, and looking for holes in the methods and results of reported experiments. Authors' responsibilities include submitting manuscripts with scientific integrity and being ready to take responsibility for their articles even long after publication. Finally, reviewers' responsibilities include identifying similar articles not cited. Reviewers are also welcome to write a discussion on the article they review.